Responses of cassava growth and yield to leaf harvesting frequency and NPK fertilizer in South Kivu, Democratic Republic of Congo - Munyahali, W.; Pypers, Pieter; Swennen, Rony L.; Walangululu, J.; Vanlauwe, Bernard; Merckx, Roel (Elsevier, 2017)
Harvesting young cassava leaves as a vegetable is a common practice in the Democratic Republic of Congo (DR Congo). However, information on its effects on growth and yield of cassava is scarce. Multi-locational trials were conducted on farmers’ fields in the province of South Kivu, DR Congo, during two consecutive years to investigate the effects of harvesting frequency of 3 young leaves (no leaf harvesting (NoH); leaf harvesting at 4 week intervals (4-WI) or 2 week intervals (2-WI), starting 4 months after planting) and fertilizer (with or without NPK application) on the growth and yields of cassava, comparable to common practice by farmers in the area, based on a preceding household survey. Overall, harvesting of leaves did not result in significant effects on both height and stem diameter compared with the unharvested treatment. However, collection of leaves at 2-WI significantly (P < 0.05) decreased both height and stem diameter, and resulted in significant (P < 0.1) reduction of stem yields of 20.9% (4.0 t ha‐1) relative to leaf harvesting at 4-WI but only in the second year. Average total biomass and storage root yields in the control treatment were 35.8 and 23.5 t ha−1, respectively and were not significantly affected by leaf harvesting. Application of NPK fertilizer resulted in significant (P < 0.05) increases of both height and stem diameter over time, independent of the frequency of leaf harvesting. Mineral fertilizer significantly (P < 0.05) increased the overall total, storage root and stem yields by 28.3% (9.5 t ha−1), 19.9% (4.5 t ha−1) and 45.1% (5.0 t ha−1), respectively regardless of the frequency of leaf harvesting. This study indicates that harvesting of young leaves results in small or negligible effects on cassava growth and yields compared to the mineral fertilizers which increase both cassava growth and yields in the conditions of our study.